Fundamentals of Nursing : Caring and Clinical Judgment - Harkreader, Helen; Hogan, Mary Ann (Missouri : Saunders, 2004)
Provides comprehensive coverage of nursing concepts and skills for RN students. Each chapter begins with a case study and an overview of key nursing diagnoses, and presents assessment, planning, interventions, and evaluation within the context of the client in the case study and these diagnose
Keywords: Nusing; Nursing -- Practice; Clinical Judgment